The Challenges of implementing active labour market policies in Cambodia - BRONH, Sopheana (KDI School, 2015)
In the current economic transition, Cambodia’s labour forces are moving from the subsistent agricultural sector to the modern sectors, in which skilled workers are required. However, this country is abundant in low skill, and low productivity labour forces resulting in skill shortages and skill gaps. Development experiences show that these problems can be solved with well-designed Active Labour Market Policies (ALMPs), especially with the Technical Vocational Education and Training (TVET), and the Public Employment Service (PES). However, the two systems are currently not working well in the Kingdom. By using qualitative approaches, this study is trying to identify current situation and the key challenges of TVET and PES. The research finds some improvements, thanks to the efforts of the Cambodian government, and the critical challenges in the current systems. Among others, the challenges of geographical setting, human resources, financial resources, research and development (R&D), and public-private partnership (PPP) are discussed. To solve the above-mentioned issues, the study makes an attempt to present the policy recommendations for the Cambodian government as a means to improve the quality of labour forces with the well-designed TVET and PES for the future sustainable economic development.
Thesis(Master) --KDI School:Master of Public Policy,2015